2001
DOI: 10.1073/pnas.071055798
|View full text |Cite
|
Sign up to set email alerts
|

ANX7, a candidate tumor suppressor gene for prostate cancer

Abstract: The ANX7 gene is located on human chromosome 10q21, a site long hypothesized to harbor a tumor suppressor gene(s) (TSG) associated with prostate and other cancers. To test whether ANX7 might be a candidate TSG, we examined the ANX7-dependent suppression of human tumor cell growth, stage-specific ANX7 expression in 301 prostate specimens on a prostate tissue microarray, and loss of heterozygosity (LOH) of microsatellite markers at or near the ANX7 locus. Here we report that human tumor cell proliferation and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
104
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(109 citation statements)
references
References 37 publications
5
104
0
Order By: Relevance
“…Indeed, treatment of LNCaP cells, which have completely lost annexin II expression (Figure 3, this study), with the DNA methyltransferase inhibitor 5-aza-deoxycytidine reactivated the annexin II expression in these cells (Chetcuti et al, 2001), suggesting that promoter hypermethylation might be responsible for the gene silencing. Interestingly, another annexin molecule, annexin 7, is also lost in prostate cancer cells and has been proposed as a prostate tumor suppressor (Srivastava et al, 2001). Different from annexin II, the loss of annexin 7 expression appears to be because of loss of heterozygosity, thus indicative of gene mutations (Srivastava et al, 2001).…”
Section: Annexin II Inhibits Migration Of Prostate Cancer Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, treatment of LNCaP cells, which have completely lost annexin II expression (Figure 3, this study), with the DNA methyltransferase inhibitor 5-aza-deoxycytidine reactivated the annexin II expression in these cells (Chetcuti et al, 2001), suggesting that promoter hypermethylation might be responsible for the gene silencing. Interestingly, another annexin molecule, annexin 7, is also lost in prostate cancer cells and has been proposed as a prostate tumor suppressor (Srivastava et al, 2001). Different from annexin II, the loss of annexin 7 expression appears to be because of loss of heterozygosity, thus indicative of gene mutations (Srivastava et al, 2001).…”
Section: Annexin II Inhibits Migration Of Prostate Cancer Cellsmentioning
confidence: 99%
“…Interestingly, another annexin molecule, annexin 7, is also lost in prostate cancer cells and has been proposed as a prostate tumor suppressor (Srivastava et al, 2001). Different from annexin II, the loss of annexin 7 expression appears to be because of loss of heterozygosity, thus indicative of gene mutations (Srivastava et al, 2001). It is of interest to note that S100A2, which, like p11 or S100A10, belongs to the S100 family of proteins, is also reduced in LNCaP cells (protein spot 4 in Figure 1b, panel d), as observed in breast cancer cells (Lee et al, 1992) and recently reported by others in prostate cancer cells (Gupta et al, 2002).…”
Section: Annexin II Inhibits Migration Of Prostate Cancer Cellsmentioning
confidence: 99%
“…TP53 (14) and PTEN (15) are among tumour suppressor genes shown to be inactivated in prostate cancer. Comparative genomic hybridization (CGH) and loss of heterozygosity (LOH) analyses suggest further oncogenes and tumour suppressor genes (16)(17)(18)(19)(20) (reviewed in ref. 21).…”
Section: Introductionmentioning
confidence: 99%
“…For example, mapping of loss within the chromosome 10 region demonstrated that SFTPA1 and SFTPA2 were deleted, but that the flanking genes PPIF and Q9NQE0 were not tract and the prostate, and has been proposed to have a role in innate immune response (Khubchandani and Snyder, 2001). The SFTPA1 and SFTPA2 genes located at map position 89 Mb are flanked by two genes that have already been proposed as prostate cancer suppressor genes: the PTEN gene at 93 Mb and the ANX7 gene at 78 Mb (Li et al, 1997;Srivastava et al, 2001).…”
mentioning
confidence: 99%